ORIENTASI HAPPINESS PADA ORANGTUA YANG MEMILIKI ANAK TUNAGRAHITA RINGAN - Na'imah, Tri; Nur'aeni, Nur'aeni; Septiningsih, Dyah Siti (Jurnal Psikologi, 2017)
The purposes of this study were: 1) assess the orientation of happiness in mothers of children with mild mental retardation, 2) assess the orientation of happiness in the fathers who have children with mild mental retardation. This study is a qualitative study using phenomenological approach. The primary informants are mothers and fathers who have mild mentally disabled children who attend school in SLB C Yakut Purwokerto, while the secondary informants were neighbors. Methods of data collection in this study is the interview. Analysis of the data used interactive model analysis. The results showed: There are differences in the pattern of happiness orientation between the mother and father who have children with mild mental retardation. Orientation mother more happiness are dominated on social engagement, meaning that mother happier if it can be involved in social activities. While the pursuit of happiness if dad can do something fun that is the way the economic needs of the family.